Sturge Weber syndrome, when brain CT is enough for diagnosis: about a case - Niang, Ibrahima (Pan Afr Med J, 2020)
One of the main manifestations of Sturge Weber syndrome is seizures. We report the case of a child received in the context of generalized seizures and in whom a cerebral contrast CT was sufficient to make the diagnosis of Sturge Weber syndrome.